Orbital-order as the driving mechanism for superconductivity in ruthenates - Álvaro Adrián Carrasco Álvarez; Sébastien Petit; Wilfrid Prellier; Manuel Bibes; Julien Varignon (Nature Communications)
Abstract Several materials transition from an insulating to a superconducting state by reducing the strength of the electron-phonon coupling associated with charge and bond orderings provided that the coupling remains strong enough to produce Cooper pairs. While the Jahn-Teller effect is at the core of a strong electron-phonon coupling producing insulating states and orbital and bond orderings, its implication in superconductivity remains unobserved. Here, with parameter-free first-principles calculations, we reveal that superconductivity in A2RuO4 (A = Sr, Ca) emerges due to an electron-phonon mechanism associated with the proximity of an orbital and bond-ordered phase. The model predicts critical temperatures T c of 0.5–1.65 K in bulk Sr2RuO4 and 63–73 K in pressured Ca2RuO4, in agreement with experiments. Our results suggest that phonons strongly coupled to electrons, such as those involved in charge disproportionation or Jahn-Teller effects and inducing band gaps in various oxides, could also serve as mediators of Cooper pairs in metallic phases.